4 - Morphologie du quotidien, souffrance sociale et parcours individuels au Cameroun: la mort de Monique Koumatekel, un problème social ? - Jacquineau Azétsop,; Christophe Tchawa,; Sylvestre Omgba Essomba, (African Sociological Review, 2018)
This paper starts with the “Koumatekel drama” and establishes a link between individual trajectories and social suffering through a critical reflection on everyday life in Cameroon. This drama refers to the personal experience of a young pregnant woman, Monique Koumatekel, who dies within the compound of a referral hospital in Douala in front of an indifferent medical staff. The niece of the deceased, in a desperate attempt to save the two fetuses, disembowels her. The image of Monica’s death body circumnavigated the web and the local and international press. This drama turned out to be a moment of truth for the entire Cameroonian society through the political and social mobilization it sparked. Beyond the buzz it provoked, this drama uncovers a deeper which is about how the therapeutic and social trajectory of Monique retraces the daily path of ordinary citizen; a path informed, at the individual level by survivals logics and, at the social level, by those of the socio-political exclusion. Social suffering, that frames individual trajectories, is the product of structural violence. Hence, the malfunctioning of the Cameroonian health system, that failed Koumatekel, is nothing other than the reflection of the dysfunction of the entire social system.